2018
DOI: 10.1039/c7tc05366e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optoelectronic performance in AgBiS2 nanocrystals obtained via an improved amine-based synthesis route

Abstract: Solar cells fabricated using modified AgBiS2 nanocrystals achieved a PCE of 4.3%, which is a 30% improvement compared with conventional AgBiS2 nanocrystal solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 35 publications
0
54
0
Order By: Relevance
“…Monodisperse colloidal NCs as a light-absorbing layer provide reduced energetic disorder and band tail broadening, both of which are urgently required to improve solar cell performance. [24][25][26][27][28] The use of oleylamine in previous oleate-based synthetic routes enables improved monodispersity of AgBiS 2 NCs because the oleylamine not only helps the Ag precursor to completely dissolve, but also provides an efficient surface passivation of the AgBiS 2 NCs with oleic acid. 28 Surface ligands with various functional groups such as thiol, amine, and carboxylate greatly affect the chemical and physical properties of the resultant semiconducting colloidal NCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monodisperse colloidal NCs as a light-absorbing layer provide reduced energetic disorder and band tail broadening, both of which are urgently required to improve solar cell performance. [24][25][26][27][28] The use of oleylamine in previous oleate-based synthetic routes enables improved monodispersity of AgBiS 2 NCs because the oleylamine not only helps the Ag precursor to completely dissolve, but also provides an efficient surface passivation of the AgBiS 2 NCs with oleic acid. 28 Surface ligands with various functional groups such as thiol, amine, and carboxylate greatly affect the chemical and physical properties of the resultant semiconducting colloidal NCs.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] The use of oleylamine in previous oleate-based synthetic routes enables improved monodispersity of AgBiS 2 NCs because the oleylamine not only helps the Ag precursor to completely dissolve, but also provides an efficient surface passivation of the AgBiS 2 NCs with oleic acid. 28 Surface ligands with various functional groups such as thiol, amine, and carboxylate greatly affect the chemical and physical properties of the resultant semiconducting colloidal NCs. 28,29 In particular, the ligand binding sites and energies on NC surfaces vary according to the functional groups of the surface ligands, indicating that these groups undergo different ligand exchange mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a strive for nontoxic, earth‐abundant solar cell materials. A very promising solar cell material consists of AgBiS 2 nanocrystals . Recently, a solar cell based on AgBiS 2 nanocrystals has been demonstrated with a certified power conversion efficiency of 6.3%, for an active film thickness of only 35 nm .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, AgBiS 2 nanocrystals (NCs) have emerged as a candidate lead-free inorganic PV material, because the nanocrystals are composed of non-toxic and earth-abundant elements. [19][20][21] Applications of AgBiS 2 NCs as a solar-cell material were rst reported by Bernechea et al in 2016, although the synthesis of AgBiS 2 bulk and nanocrystal materials has been reported much earlier. 19 Bernechea et al demonstrated a certied PCE of 6.3% for AgBiS 2 NCs based solar cells fabricated at the ambient pressure and at temperatures below 100 C. Note that all elements (Ag, Bi, and S) in AgBiS 2 NCs are earth-abundant.…”
Section: Introductionmentioning
confidence: 93%